Spontaneous happiness [large type] - Weil, Andrew (Little, Brown and Co., 2011)
This book presents integrative treatment strategies for low mood and depression; offers advice on lifestyle, behavior, and dietary changes; and helps readers assess their own emotional wellness and build personalized plans to manage their moods.